2021
DOI: 10.1177/15347354211037938
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy in Head and Neck Cancer-Related Lymphedema: A Pilot Feasibility Study

Abstract: Purpose: Lymphedema is a common debilitating late effect among patients post-head and neck cancer (HNC) treatment. Head and neck lymphedema was associated with symptom burden, functional impairment, and decreased quality of life. The objective of this study was to determine the feasibility and potential efficacy of the use of photobiomodulation (PBM) therapy for head and neck lymphedema, symptom burden, and neck range of motion among HNC survivors. Methods: This was a single-arm, pre- and post-design clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Of 1642 unique citations identified by the search, 24 citations (1.5%) met the inclusion criteria, representing 23 unique studies (n = 2147 patients); 1 study produced 2 unique citations that reported different outcomes . Of the 23 studies, 6 were RCTs (26.1%) and 17 (73.9%) were observational studies (Figure).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 1642 unique citations identified by the search, 24 citations (1.5%) met the inclusion criteria, representing 23 unique studies (n = 2147 patients); 1 study produced 2 unique citations that reported different outcomes . Of the 23 studies, 6 were RCTs (26.1%) and 17 (73.9%) were observational studies (Figure).…”
Section: Resultsmentioning
confidence: 99%
“…The median number of participants was 34 (range, 7-1202). Most studies had fewer than 50 participants (12 of 17 studies). Anatomical disease sites were mixed HNC in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants also reported saving time and travel expense, issues that were particularly important to participants living outside of Philadelphia. Travel time and distance are common reasons why potential participants declined to participate in the study before the pandemic [10]. The advantage of using telehealth is that it allows patients to easily access resources from wherever they are located, thus leading to more patient involvement.…”
Section: Lessons Learnedmentioning
confidence: 99%